Aldous Huxley - Bloom, Harold (Philadelphia : Chelsea House, 2003)
Presents twelve critical essays on the writings of twentieth-century English author Aldous Huxley, and includes a chronology of his life, a bibliography, and an introduction by Harold Bloom.
Introduction / Harold Bloom -- Marking and remembering: Aldous Huxley / Milton Birnbaum -- Brave new world and the flight from God / John Attarian -- Color and light: Huxley's pathway to spiritual reality / Sally A. Paulsell -- Aldous Huxley's modern myth: Leda and the poetry of ideas / Jerome Meckier -- Aldous Huxley, satiric sonneteer: the defeat of youth / Jerome Meckier -- Aldous Huxley in Russia / Nina Diakonova -- Golding and Huxley: the fables of demonic possession / James R. Baker -- Aldous Huxley and the nuclear age: ape and essence in context / Sanford E. Marovitz -- Westward utopia: Robert V. Hine, Aldous Huxley, and the future of California history / Kerwin Lee Klein -- The best of companions: J. W. N. Sullivan, Aldous Huxley, and the new physics / David Bradshaw -- Aldous Huxley's philosophy / Ronald Hope -- Huxley's "deep jam" and the adaptation of Alice in wonderland / David Leon Higdon -- Brahmins from abroad: English expatriates and spiritual consciousness in modern America / David Robb.
Includes bibliographical references (p. 223-225) and index.
Young Adult.
Young Adult
Keywords: Huxley, Aldous, -- 1894-1963 -- Criticism and interpretation; Huxley, Aldous, -- 1894-1963 -- Criticism